Tertúlia a constituição de sujeitos no processo de construção de sentidos sobre a arte - Pedro, Luciana Guimarães (2013)
Considering that art can collaborate in the formation of the person, this dissertation aimed to understand how subjects are constituted from the construction and sharing of meanings about art in a group setting. Inspired by the method proposed by Historical Dialectic Materialism, this research took as its starting point the construction of a group called Tertúlia , composed of ten students of psychology undergraduate of the Federal University of Uberlândia, and researcher in question, in order to appreciate art in its different manifestations, and discuss the meanings constructed from this experience. So, to make up the research corpus of this investigation, the group meetings were recorded by a camcorder and then transcribed as written text narrative; and in addition, the analyzed material was also composed by two letters made by tertuliano and a portfolio to bring, in a creative and authorial way, the personal record of the most significant experiences they lived in group. To understand of this phenomenon, I dedicated myself to the theoretical study of the constitution of the subject in cultural-historical perspective of semiotic mediation, the attribution of meaning in the process of signification, the concept of Imminent Development Zone and art as a product of social life. Later, trying to relate the reality investigated and the fundamental concepts in this work, four categories explanatory were delimited, which I have called clustered senses. These categories grouped the senses expressed by participants that related art to personal experiences; the art of the general aspects of life; art, culture and society; and finally, art and other human productions. The analysis of the excerpts that evidenced the transformations experienced by the participants pointed to the importance of a collective space to enjoy art in the process of constitution of the person, besides enabling reflections on the importance of sharing the senses with the other, in the process of transformation of the subject; the place of art in the university and the current model of education, considering the capitalist way of life; the possibility of developing new ways of organizing thought from the exchange of meanings about art; the contributions of the enjoyment of art in the process of reframing and establishing new ways of acting in the world and, finally, about the social role of art and its role as a mediator in the process of autonomy the subject.